Evaluating National Preventive Mechanisms: A Conceptual Model. (10th October 2020) - Carver, Richard; Handley, Lisa
Abstract: This article outlines a rigorous and systematic approach to evaluating both the performance and impact of national preventive mechanisms (NPMs) formed under the Optional Protocol to the Convention against Torture. Many human rights practitioners remain sceptical about both the desirability and feasibility of evaluating human rights work. One obstacle has been that 'indicators' of human rights progress are formulated without evidence that they actually have a causal relationship to the intended outcome. By contrast, the tools used in this assessment model are derived from scientific research into what forms of torture prevention actually work, meaning that greater weight can be assigned to more effective activities (and vice versa). The model is piloted in an assessment of the performance and impact of the Georgian NPM, which in ten years of work is shown to have had a significant impact in reducing the incidence of torture and other ill-treatment, particularly in police detention and prisons.